Serious Educational Digital Games - Nassar, Roula (Beirut University of Balamand. Faculty of Arts and Social Sciences, department of Education, 2007)
Fully integrated into the everyday lives of millions of young people throughout the world, computer games are a vital part of contemporary culture and society. But the reaction of many authorities and the majority of educators has been to discredit computer games by assuming their negative effects. After more than two decades of research, however, many studies have been published that have gradually led to a more complex, nuanced, and useful understanding of video games. As foreseen by visionaries in the 20th century, mastery of the dynamic processes that underpin the acquisition and manipulation of knowledge is quickly becoming a critical capability in the 21st century. Our formal educational systems do not tend to facilitate the development of these capabilities, yet people of all ages are developing them via a variety of digitally-mediated mechanisms. Serious games offer one area of exploration for spontaneously-occurring phenomena that represent the natural development of such literacy.This thesis reviews the need for 21st-century skills and illuminates existing digital domains in which these skills develop organically. Peering through the window of the present into the future, we present a view that envisioning change means taking a look at what is working now.
: Mémoire
Keywords: Education et la technologie; ICT and Education Play and games; Jouer et jeux